Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kualitas dan Produktivitas Susu Sapi: Sebuah Studi Literatur - Zainarti Zainarti; Miratul Imaniah; Aulia Syahfitri; Nurhidayah Nurhidayah; Mulia Syahputri; Maysa Chairani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study uses a qualitative method and starts from the title “The Role of Human Resource Management in Improving the Quality and Productivity of Cow’s Milk: A Literature Study”. This study aims to examine in depth how human resource (HR) management plays a role in improving the quality and productivity of cow’s milk through a literature review. Effective HR management, such as employee placement according to workload, ongoing training, and competency development, has been shown to increase production efficiency and the quality of cow's milk. In addition, factors such as health management, technology utilization, and work environment management are also important aspects in supporting dairy farm productivity. This literature study found that the synergy between HR management and optimization of internal resources, such as finance, technology, and physical, contributed significantly to the development of dairy farming businesses and the achievement of sustainable milk production standards. Thus, an integrated HR management strategy is needed to answer the challenges and demands of the ever-growing market in the dairy farming sector.